ANALISIS STRATEGI BERSAING PADA TOKO SEMBAKO ABDI DI KECAMATAN CAMBAI KOTA PRABUMULIH DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Ernawati; M. Robby Kaharudin; Zayudi; Yeni Gustiana (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2023)
This study aims to determine the application of competitive strategy at Abdi Grocery Store. And whether the competitive strategy applied to the Abdi Grocery Store is in accordance with the perspective of Islamic business ethics.This research is a field research that uses a qualitative descriptive approach. Sampling techniques in this study are purposive sampling and snowball sampling. Data collection techniques through interviews, observation and documentation. Primary data is obtained from Abdi Food Store Owners, Employees and Customers who are selected based on certain conditions.The results of the Generic Strategy analysis show that Abdi's Sembako Store uses a Cost Advantage Strategy by providing low prices and providing discounts, a Differentiation Strategy by providing unique services and offering substitute products for certain circumstances and a Differentiation Focus Strategy by providing unique services to a particular segment. The competitive strategy at the Abdi Grocery Store shows a very good success, due to the increasing turnover and increasing number of customers. The owner of the Abdi Grocery Store also always instills honesty and courtesy to employees in providing services in a manner that is in accordance with the perspective of Islamic business ethics.